Information dynamics in judo - Nakagawa, T. R. M.; Minatoya, H. (Research Journal of Budo, 2015)
This paper is concerned with analyses of judo games using the information dynamic model; ?=?m, where ? is the certainty of game outcome, ? the normalized game length, and m the positive real number. It has been recognized that the proposed method of analyses is extremely useful for interpreting judo games, so judokas as well as instructors can use this model for improving their performance. The usefulness for incorporating knowledge of dynamics into the information world has been satisfactorily demonstrated through two case studies; the Final of the 5th Judo World Championship, and the Final of the 6th Judo World Championship. It was found that the cross point between the certainty of game outcome and the uncertainty of game outcome has critical meaning in a game. That is, game outcome is known at this cross point, so it has therefore been coined "game point".